2010
DOI: 10.1007/s10714-010-1125-y
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic dark energy models with constant deceleration parameter

Abstract: We consider a spatially homogeneous and totally anisotropic Bianchi-I space-time with perfect fluid (dark matter and standard visible matter) and anisotropic dark energy, which has dynamical energy density. The two sources are assumed to interact minimally and therefore their energy momentum tensors are conserved separately. Using suitable physical assumptions, the field equations are solved exactly. Various dark energy models are studied and it is found that quintessence model is suitable for describing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…They considered a phenomenological parameterization of minimally interacting DE in terms to its EoS parameter and timedependent skewness parameters. Kumar and Singh [16] have investigated a spatially homogeneous and anisotropic Bianchi type -1 model with perfect fluid composed of DE and standard visible matter. Pradhan et al [17] have studied a class of DE models of Bianchi type I with variable EoS parameter and constant deceleration parameter.…”
Section: Introductionmentioning
confidence: 99%
“…They considered a phenomenological parameterization of minimally interacting DE in terms to its EoS parameter and timedependent skewness parameters. Kumar and Singh [16] have investigated a spatially homogeneous and anisotropic Bianchi type -1 model with perfect fluid composed of DE and standard visible matter. Pradhan et al [17] have studied a class of DE models of Bianchi type I with variable EoS parameter and constant deceleration parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, ω cannot cross −1 for quintessence or phantoms alone. Ray et al (2010), Kilinc (2010a, 2010b), Pradhan et al (2010), , , , , Yadav (2011), Kumar and Singh (2011), , Kumar and Yadav (2011), Kumar (2011), Chandel et al (2012bChandel et al ( , 2014, Adhav (2012), Adhav et al (2013b), Pradhan (2013), Mishra and Biswal (2014) are some of the authors who have obtained dark energy models with variable EoS parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Setare [64][65][66] and Setare and Saridakis [67][68][69] have also studied the DE models in different contexts. Recently, dark energy models with variable EoS parameter have been studied by Ray et al [70], Akarsu and Kilinc [71][72][73][74], Yadav et al [75], Yadav and Yadav [76], Yadav and Saha [77] Pradhan and Amirhashchi [78,79], Pradhan et al [80][81][82], Amirhashchi et al [83][84][85][86], Kumar [87,88], Kumar and Akarsu [89], Kumar and Yadav [90] and Kumar and Singh [91]. In well known reviews on modified gravity [92,93], it is clearly indicated that any modified gravity may be represented as effective fluid with time dependent ω.…”
Section: Introductionmentioning
confidence: 99%
“…Here m = 1, κ = 0.5, ᐉ 1 = 1.3.From Eqs (91),. it is noted that the energy density of the fluid ρ(t) is a decreasing function of time and ρ(t) > 0 under condition(105) …”
mentioning
confidence: 98%